2016
DOI: 10.3329/bjsr.v28i2.26783
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of flood on Char livelihoods and its adaptation techniques by the local people

Abstract: The study showed that most of the farmers (81.81%) in char area of flood lands were affected by flood as their crops were washed away by flood water as agricultural lands (59%) were inundated in a high magnitude flood. During flood, almost 88.89% farmers pass their days having no alternative occupation, and cannot afford to meet basic needs of their family as most of the Char lands were inundated for about two or three months, resulting in no crop production during that period. People reside in roads, schools … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
3
1

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(11 citation statements)
references
References 6 publications
0
8
0
Order By: Relevance
“…Other places in Assam along the Brahmaputra River (Sharma et al, 2010) and districts like Barpeta (Khan, 2012) and Golaghat (Mili, Acharjee, & Konwar, 2013) faced destructions of road networks, educational infrastructure, homes and agricultural lands. Heavy losses in terms of crops, crop lands, homesteads, livestock and personal property were recorded in the Indian states of Assam (Dekaraja & Mahanta, 2021;Dutta et al, 2020) and Shantipur, West Bengal (Chatterjee & Mistri, 2013) and Bangladesh's Bhola , Mymensingh (Islam, Parvin, & Farukh, 2017), Satkhira, Bagerhat (Islam, 2012b) and Sirajgonj (Rabbi, Saifullah, Sheikh, Sarker, & Bhowmick, 2013) districts, Radhanagar, Bashuria (Islam, Parvin, Emu, & Kabir, 2019a) and Nolian villages (Khan, Nabia, & Rahman, 2018), Durgapasha union (Roy et al, 2017), Kazipur (Haque, 1997;Haque & Zaman, 1989), the Lower Teesta Basin (Ferdous & Mallick, 2019) and floodplains and coastal areas of Bangladesh (Islam et al, 2019b). The vulnerability of the char lands in Bangladesh was underlined by Islam, Singh, Shaheed, & Wei (2010) and Poncelet, Gemenne, Martiniello, & Bousetta (2010) where settlements, various infrastructure and most of all, agricultural lands were lost.…”
Section: Physical Vulnerabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…Other places in Assam along the Brahmaputra River (Sharma et al, 2010) and districts like Barpeta (Khan, 2012) and Golaghat (Mili, Acharjee, & Konwar, 2013) faced destructions of road networks, educational infrastructure, homes and agricultural lands. Heavy losses in terms of crops, crop lands, homesteads, livestock and personal property were recorded in the Indian states of Assam (Dekaraja & Mahanta, 2021;Dutta et al, 2020) and Shantipur, West Bengal (Chatterjee & Mistri, 2013) and Bangladesh's Bhola , Mymensingh (Islam, Parvin, & Farukh, 2017), Satkhira, Bagerhat (Islam, 2012b) and Sirajgonj (Rabbi, Saifullah, Sheikh, Sarker, & Bhowmick, 2013) districts, Radhanagar, Bashuria (Islam, Parvin, Emu, & Kabir, 2019a) and Nolian villages (Khan, Nabia, & Rahman, 2018), Durgapasha union (Roy et al, 2017), Kazipur (Haque, 1997;Haque & Zaman, 1989), the Lower Teesta Basin (Ferdous & Mallick, 2019) and floodplains and coastal areas of Bangladesh (Islam et al, 2019b). The vulnerability of the char lands in Bangladesh was underlined by Islam, Singh, Shaheed, & Wei (2010) and Poncelet, Gemenne, Martiniello, & Bousetta (2010) where settlements, various infrastructure and most of all, agricultural lands were lost.…”
Section: Physical Vulnerabilitymentioning
confidence: 99%
“…Another study on Malda showed that the displaced population with low levels of educational attainment found it difficult to secure a decent living (Das et al, 2017). Lower levels of schooling also obscured the ability of the people to predict or forecast riverbank erosion and its tendencies (Islam et al, 2019a) which restricted the erosion victims to prepare themselves better to face, cope and mitigate the disaster.…”
Section: Social Vulnerabilitymentioning
confidence: 99%
“…Quite apart from the fallouts of the current COVID pandemic, the ambitious plans for a Golden Bengal ( Sonar Bangla ) have not materialised earlier (Jamwal, 2004: 13), partly due to disasters related to climate change. These include more severe floods than earlier, cyclones, riverbank erosions and landslides (Government of Bangladesh, 2009; Hossain et al, 2020: 1; Islam et al, 2015), while the risks of drought were examined by Shahid and Behrawan (2008). High population density and hazardous ecological conditions subject millions of rural Bangladeshis to destruction of their farms and livelihoods, forcing many to move (Government of Bangladesh, 2009; Kabir et al, 2018).…”
Section: Prevailing Scenario On Either Side Of the Borderlandmentioning
confidence: 99%
“…However, the city lacks adequate retention and detention capacity of rainwater and sustainable development of the drainage system during urban planning and design (Mowla & Islam, 2013). Several studies have addressed water logging hazards and risks of south-west and south-east coastal zones, at different river basins of Bangladesh adapting mixmethod approach and GIS-remote sensing techniques (Hassan & Mahmud-ul-islam, 2014;Rahman et al, 2009;Tareq et al, 2018;Islam et al, 2020;Huda et al, 2022). However, to the best of our knowledge, no studies have evaluated water logging hazards through the lens of GIS and remote sensing integrated approach and have not emphasized the contribution of rapid urbanization.…”
Section: Introductionmentioning
confidence: 99%